2012
DOI: 10.1016/j.celrep.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Maturation-Promoting Activity of SATB1 in MGE-Derived Cortical Interneurons

Abstract: SummaryThe generation of cortical interneuron subtypes is controlled by genetic programs that are activated in the ventral forebrain and unfold during the prolonged period of inhibitory neuron development. The LIM-homeodomain protein LHX6 is critical for the development of all cortical interneurons originating in the medial ganglionic eminence, but the molecular mechanisms that operate downstream of LHX6 to control the terminal differentiation of somatostatin- and parvalbumin-expressing interneurons within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(133 citation statements)
references
References 57 publications
5
128
0
Order By: Relevance
“…SATB1 binds to genomic loci of multiple immediate early genes (IEGs) and is required for the proper temporal expression of these genes during postnatal development. SATB1 is also induced by neuronal activity and promotes interneuron maturation (27,28). However, the role of SATB1 in neural stem cell differentiation during embryonic or adult neurogenesis has not been uncovered and our study provides the first evidence for the role of SATB1 in adult neurogenesis.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…SATB1 binds to genomic loci of multiple immediate early genes (IEGs) and is required for the proper temporal expression of these genes during postnatal development. SATB1 is also induced by neuronal activity and promotes interneuron maturation (27,28). However, the role of SATB1 in neural stem cell differentiation during embryonic or adult neurogenesis has not been uncovered and our study provides the first evidence for the role of SATB1 in adult neurogenesis.…”
Section: Discussionmentioning
confidence: 69%
“…S5B), we decided to investigate transcription factors among predicted HuD targets to identify a novel regulatory network between HuD and transcriptional regulators in neural differentiation. Among the transcription factors on the HuD target list, we focused on SATB1 because of its known function in regulating cell linage-specific gene expression during both T-cell development (26) and cortical neuron maturation (27,28). We first assessed the expression of SATB1 and confirmed that it was localized in Nestin +…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Arx transduction of Lhx6 mutant MGE cells restored ~25% of the SST cells (Figures 4E′ and 4N′: p = 0.01) and ~80% of the PV cells (Figures 4K′ and 4O′: p = 0.002). Denaxa et al (2012) found that Satb1 is downstream of Lhx6 and promotes SST expression. We also detected loss of Satb1 expression in Lhx6 mutants (Figures S5A–S5F) but Arx transduction did not rescue Satb1 expression in Lhx6 mutants (Figures S5G–S5L).…”
Section: Resultsmentioning
confidence: 98%
“…However, MGE-derived interneurons from Lhx6 mutants fail to occupy middle neocortical layers and exhibit a preference for superficial and very deep layers (Liodis et al, 2007; Zhao et al, 2008). While Lhx6 promotes the expression of several genes that control cell fate and migration, including Arx, Sox6, CXCR7 (Flandin et al, 2011; Zhao et al, 2008), and Satb1 (Close et al, 2012; Denaxa et al, 2012), only the role of Satb1 in the Lhx6 phenotype has been evaluated.…”
Section: Introductionmentioning
confidence: 99%